2024
DOI: 10.1186/s13287-024-03684-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple treatments with human embryonic stem cell-derived mesenchymal progenitor cells preserved the fertility and ovarian function of perimenopausal mice undergoing natural aging

Eun-Young Shin,
Suji Jeong,
Jeoung Eun Lee
et al.

Abstract: Objectives Currently, no approved stem cell-based therapies for preserving ovarian function during aging. To solve this problem, we developed a long-term treatment for human embryonic stem cell-derived mesenchymal progenitor cells (hESC-MPCs). We investigated whether the cells retained their ability to resist ovarian aging, which leads to delayed reproductive senescence. Materials and methods In a middle-aged female model undergoing natural aging, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Notably, long-term treatment with hESC-MPCs decreased the population of myeloid-derived suppressor cells (MDSCs), which increase with age and play a pivotal role in tissue fibrosis. This inhibitory effect on MDSC proliferation was further confirmed through in vitro co-culture of MDSCs with hESC-MPCs [50]. While the precise mechanisms by which hESC-MPCs inhibit MDSC proliferation and delay ovarian aging require further investigation, the results suggest that hESC-MPCs could play a key role in combating ovarian and biological aging.…”
Section: Hpsc-mpc Therapy For Functional Recovery Of Naturally Aged O...mentioning
confidence: 73%
See 2 more Smart Citations
“…Notably, long-term treatment with hESC-MPCs decreased the population of myeloid-derived suppressor cells (MDSCs), which increase with age and play a pivotal role in tissue fibrosis. This inhibitory effect on MDSC proliferation was further confirmed through in vitro co-culture of MDSCs with hESC-MPCs [50]. While the precise mechanisms by which hESC-MPCs inhibit MDSC proliferation and delay ovarian aging require further investigation, the results suggest that hESC-MPCs could play a key role in combating ovarian and biological aging.…”
Section: Hpsc-mpc Therapy For Functional Recovery Of Naturally Aged O...mentioning
confidence: 73%
“…Human MPCs derived from various sources, including adult tissues, fetal tissues, and PSCs, have been proposed as novel therapeutic agents for treating a range of diseases, such as reproductive senescence. In this review article, we discuss how hESC-MPCs may help preserve ovarian function (Table 1) and delay reproductive senescence in both chemotherapy-induced and naturally aging perimenopausal female mice [34,50,51]. Furthermore, a previous study indicated that the secretome of hESC-MPCs could prevent ovarian dehttps://doi.org/10.5653/cerm.2024.07003 generation and help maintain female fecundity when these cells were locally administered in a chemotherapy-induced mouse model [42].…”
Section: Further Consideration Of Hpsc-derived Mpc Therapy For Recove...mentioning
confidence: 99%
See 1 more Smart Citation